Activating values intervention: an integrative pathway to well-being - Russo-Netzer, Pninit; Atad, Ofer Israel (Frontiers in Psychology, 2024)
The present study expands the existing knowledge base regarding positive psychology interventions (PPIs), by employing an integrative approach to explore the potential benefits of translating values into action. Participants (n=476) were randomly assigned to the Activating Values intervention, affirmation-only, or the control-no treatment group. The intervention involved participants choosing a life area they valued, affirming its importance, identifying a specific action related to that valued area, and then planning and carrying out that chosen action within the following week. Data was collected at baseline and three follow-up points: one, two, and three weeks after the intervention. Results suggest that the intervention contributes to the participants' well-being, including increased self-insight, sense of coherence, and prioritizing meaning, and decreased symptoms of psychopathology. Exploratory content analyses provide a deeper understanding of the content and frequency of activities chosen and the enabling conditions. The discussion explores the findings within this intersection as well as ramifications for brief, scalable interventions to support and promote well-being.